Within and Between Firm Trends in Job Polarization: Role of Globalization and Technology - Sari Pekkala Kerr; Terhi Maczulskij; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2016)
This paper analyzes occupational polarization within and across firms using comprehensive matched employer-employee panel data from Finland. The occupational distribution in Finland has been polarizing over the last few decades, with mid-level production and clerical jobs eroding while low-skill service occupations and high-skill specialist occupations gain share. We find that the phenomenon is taking place within existing firms, as well as due to firm entry and exit. Service jobs are increasing through the entry-exit dynamics, but also via establishment level restructuring among continuing firms. Routine jobs, including mid-level plant operating jobs, are being destroyed both among continuing firms and at the entry-exit margin. The share of high-level occupations increases largely within continuing firms. Within the continuing firms the job polarization appears to be related to the trade of goods and services, as well as the outsourcing of tasks. Firms with high R&D expenditures and ICT use are more prone to lay off process and production workers.
Keywords: J24; J31; O33; 330; Job polarization; offshoring; international trade; firm; establishment; technology; R&D; ICT